The Protective Effects of Neighborhood Collective Efficacy on Adolescent Substance Use and Violence Following Exposure to Violence - Fagan, Abigail A. (2013)
Research has demonstrated that exposure to violence can result in many negative consequences for youth, but the degree to which neighborhood conditions may foster resiliency among victims is not well understood. This study tests the hypothesis that neighborhood collective efficacy attenuates the relationship between adolescent exposure to violence, substance use, and violence. Data were collected from 1,661–1,718 adolescents participating in the Project on Human Development in Chicago Neighborhoods (PHDCN), who were diverse in terms of sex (51% male, 49% female), race/ethnicity (48% Hispanic, 34% African American, 14% Caucasian, and 4% other race/ethnicity), and age (mean age 12 years; range: 8–16). Information on neighborhood collective efficacy was obtained from adult residents, and data from the 1990 U.S. Census were used to control for neighborhood disadvantage. Based on hierarchical modeling techniques to adjust for the clustered data, Bernoulli models indicated that more exposure to violence was associated with a greater likelihood of tobacco, alcohol, and marijuana use and perpetration of violence. Poisson models suggested that victimization was also related to a greater variety of substance use and violent behaviors. A moderating effect of collective efficacy was found in models assessing the variety of substance use; the relationship between victimization and substance use was weaker for youth in neighborhoods with higher versus lower levels of collective efficacy. These findings are consistent with literature indicating that social support can ameliorate the negative impact of victimization. This investigation extends this research to show that neighborhood social support can also help to promote resiliency among adolescents.